Effects of a paddling-based high-intensity interval training prescribed using anaerobic speed reserve on sprint kayak performance - Du, G.; Tao, T. (Frontiers in Physiology, 2023)
The aim of this study was to investigate physiological and performance adaptations to high-intensity interval training (HIIT) prescribed as a proportion of anaerobic speed reserve (ASR) compared to HIIT prescribed using maximal aerobic speed (MAS). Twenty-four highly trained sprint kayak athletes were randomly allocated to one of three 4-weak conditions (N = 8) (ASR-HIIT) two sets of 6 × 60s intervals at ?%20ASR (MAS-HIIT) six 2min paddling intervals at 100% maximal aerobic speed (MAS); or controls (CON) who performed six sessions/week of 1-h traditional endurance paddling at 70%-80% maximum HR. A graded exercise test was performed on a kayak ergometer to determine peak oxygen uptake (V?O2peak), MAS, V?O2/HR, and ventilatory threshold. Also, participants completed four consecutive upper-body wingate tests to asses peak and average power output. Significant increases in V?O2peak (ASR-HIIT = 6.9%, MAS-HIIT = 4.8%), MAS (ASR-HIIT = 7.2%, MAS-HIIT = 4.8%), ASR (ASR-HIIT = -25.1%, MAS-HIIT = -15.9%), upper-body Wingate peak power output and average power output (p < 0.05 for both HIIT groups) were seen compared with pre-training. Also, ASR-HIIT resulted in a significant decrease in 500-m (-1.9%), and 1,000-m (-1.5%) paddling time. Lower coefficient of variation values were observed for the percent changes of the aforementioned factors in response to ASR-HIIT compared to MAS-HIIT. Overall, a short period of ASR-HIIT improves 500-m and 1,000-m paddling performances in highly trained sprint kayak athletes. Importantly, inter-subject variability (CV) of physiological adaptations to ASR-HIIT was lower than MAS-HIIT. Individualized prescription of HIIT using ASR ensures similar physiological demands across individuals and potentially facilitates similar degrees of physiological adaptation.